Farming uphill - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
No right-minded farmer will switch to a different farming system overnight, even if certain changes might be for the better. Many farmers often cannot afford to invest money or take many risks, but they are interested in using gradual methods to...